Unlocking Ethiopia's Urban Land and Housing Markets : Urban Land Supply and Affordable Housing Study - World Bank Group (World Bank, Washington, DC, 2019)
The Ethiopia Urban Land Supply and Affordable Housing Study (EULSAH) responds to the request fromthe Government of Ethiopia (GoE), Ministry of Urban Development and Construction to carry outfollow-on technical assistance to the Ethiopia Urbanization Review (EUR) jointly published by theWorld Bank and the GoE in 2015. The EUR calls for a robust institutional framework to support efficient and sustainable land management and housing delivery, urban governance, and municipal finance, taking into account Ethiopia’s constitutionally entrenched system of land tenure.EULSAH aims to inform policy decisions on how to address the growing demand for urban land andaffordable housing in the context of rapid urbanization in Ethiopia. It supports two interrelatedcomponents, Urban Land and Housing. The Urban Land component has two subcomponents. The first subcomponent “Urban Land Cadaster” was successfully delivered to the GoE in May 2017. The second subcomponent “Urban Land Supply” along with the “Housing” component are featured in the EULSAH.The Ethiopia Urban Land Supply and Affordable Housing Study is a product of close collaborationbetween the World Bank and the GoE. The Terms of Reference were developed based on technicaldiscussions and numerous consultation activities with national and local government officials,including discussions with the Prime Minister and senior Cabinet members, state enterprise leaders,private sector actors and development partners. These were undertaken during the finalization of the EUR and a subsequent scoping mission in October 2015. The inception report was presented to the GoE Task Force in June 2017; this was followed by two video conferences with the task force to discuss preliminary findings from urban land supply and affordable housing respectively. A technical consultation workshop on the key findings and preliminary recommendations on policy changes and institutional reforms was held with national and urban local governments, the private sector, academics, and development partners in November 2018. A high-level national consultation workshop was held in Addis Ababa with key stakeholders for the final draft reports on May 10, 2019 to seek further feedback on the revised reports with a focus on how to move the policy recommendation forward.